Global and local forcing of Early Toarcian seawater chemistry: A comparative study of different paleoceanographic settings (Paris and Lusitanian basins) - Hermoso, M; Minoletti, F; Le Callonnec, L; Jenkyns, H; Hesselbo, S; Rickaby, R; Renard, M; de Rafelis, M; Emmanuel, L (2009)
The Early Toarcian was characterized by two large perturbations to the carbon cycle: a positive trend associated with increased organic matter burial and ocean anoxia, and a pronounced negative carbon isotope excursion (CIE). We contrast the geochemical evolution in the carbonate phases of two successions: one from the Paris Basin (Sancerre core, comprising black shales), the other from the Lusitanian Basin (Peniche section with very minor lithological expression of bottom water anoxia). Our aim was to identify whether these carbon cycle perturbations were related, and differentiate between the common (global) versus regional expressions of the biogeochemical response and ocean chemistry. Our results highlight contrasts in timing of different phases of anoxia in both locations through the widely documented negative CIE. Widespread anoxic conditions were not a necessary prerequisite for generating a pronounced CIE, as required by the recycling (so-called "Küspert") model. The production of carbonate simultaneously dropped during the δ13C negative shift in both locations, likely in response to lowered seawater saturation rate induced by substantial absorption of CO2 from the atmosphere. The recovery interval was accompanied by a rapid reestablishment of seawater alkalinity, and primary and carbonate productivity in epicontinental seas, as evidenced by high δ13C and Sr/Ca, in contrast with the more open ocean regime in the Lusitanian Basin. Our results confirm that parallels can be draw between the ocean productivity response and feedback during the Toarcian CIE and the PETM. Both events are characterized by ocean acidification and reduced pelagic calcification followed by a peak in nearshore coccolith productivity, which could have helped the recovery from the perturbation. Copyright 2009 by the American Geophysical Union.